GREENFUSION: SYNTHESIS OF NEXT-GENERATION GREEN DIESEL FUEL THROUGH HYDRODEOXYGENATION OF NYAMPLUNG AND UCO - Muhammad Ilham Rizky Maulana; Fahri Sinulingga (Institut Teknologi Sepuluh Nopember, 2026)
The urgency of the energy transition in Indonesia is becoming increasingly pressing due to the country's high dependence on fossil fuels and the presence of 5 million diesel vehicles. This research introduces